(3GdGMUGA GdGMJeGdj (B/s - (3eMeO SGde, ceGd SdWGfs ((3GdGHQGgjejI(B: s (3GdOGQ GdLGeYjI(B, s, 2004)
(3jJfGhd gPG GdcJGH GdeLehYGJ hGdGMJeGd hGdJhRjYGJ GdGMJeGdjI h GdYjfGJ hJhRjYGJ GdeYGjfg hGdJbOjQ hbO bSe Gdi eGjdj GdHGH GdChd (B: (3GdeLehYGJ hGdGMJeGd (B: (3GdeLehYGJ hJMJ GdeLehYGJ (B: (3YedjGJ GdeLehYGJ (B: (3WQb GdYO (B: (3GdGMJeGdGJ(B-(3GdHGH GdKGfj (B: (3GdJhRjYGJ GdGMJeGdjI (B: (3JegjO (B: (3GdJhRjYGJ GdGMJeGdjI GdefbWYI (B: (3GdJhRjYGJ GdGMJeGdjI GdeJUdI(B-(3GdHGH GdKGdK (B: (3GdYjfGJ hJhRjYGJ GdeYGjfI hGdJbOjQ (B: (3GdgjfGJ (B: (3JhRjYGJ GdeYGjfI (B: (3GdJbOjQ(B-(3GdHGH GdQGHY (B: (3GNJHGQGJ GdaQhV (B: (3GdGWGQ GdYGe dGNJHGQGJ GdaQhV (B: (3GNJHGQGJ GdaQhV aj MGdI GdYjfGJ GdcHjQI (B: (3GNJHGQGJ GdaQhV aj MGdI GdYjfGJ GdUZjQI (B: (3GNJHGQGJ GdaQhV aj GdYjfGJ GdJGHYI (B: (3MOhO GdKbI ddeJhSWGJ hGdfSH hGdJHGjf(B-(3GdHGH GdNGeS (B: (3JMdjd GdSdGSd GdRefjI (B: (3JbOjQ GdGJLGg GdYGe (B: (3GdJZjQGJ GdehSejI (B: (3GdHjGfGJ GdeYOdI ehSejkG (B: (3JObjQ GdJZjQGJ GdOhQjI(B-(3GdHGH GdSGOS (B: (3GdGNJHGQGJ GddGHGQGeJQjI (B: (3GNJjGQ GdYdGeI Ch GdETGQI (B: (3GNJjGQ GdYdGeI aj MGdI GdYjfGJ GdcHjQI (B: (3GNJjGQ hjdch cSf dQJH GdETGQGJ (B: (3JMdjd GdJHGjf aj MGdI GdQJH (B: (3GQJHGW GdQJH (B: (3JWHjbGJ deQHY cGS aj GdeLGd GddGHGQGeJQj(B.s
(3HjHdjhZQGajG(B: (3U(B. 370s
Keywords: (3GdGMJeGdGJs; (3GdGMUGAs; (3GdGMUGA GdQjGVjs